STUDY OF DENSE MEMBRANE DEVELOPMENT FOR SEAWATER MEMBRANE DISTILATION APPLICATIONS - Nurgirisia, Novesa
Desalination via Membrane Distillation technology has the potential to be an efficient method for obtaining clean water from seawater and other high salinity water resources. Membrane distillation has the advantages of high salt rejection and suitable for treating high salinity solutions. The phenomenon of membrane wetting is still the main drawbacks for membrane distillation operations. One of the efforts to deal the wetting problem in membrane distillation is to develop a dense membrane/non-porous membrane. Dense membrane offers anti-wetting and high salt rejection properties. However, the mass transfer resistance is another challenge for dense membranes so that many studies have been carried out to find the optimum membrane characteristics. In addition, it is very rare to use dense membranes for membrane distillation application and is not yet used commercially. This literature study focuses on providing additional insight of the mass transfer mechanism of dense membranes, dense membrane preparation strategies, as well as the development of membranes with special characteristics to overcome membrane wetting that can be considered for developing dense membranes. Based on the results of the literature studies, dense membranes are more widely applied as an active layer in composite asymmetric membranes compared to self-stand dense membranes. The dense membrane as an active layer with a thickness of less than 1 ?m can provide the same performance as a porous membrane. The mass transfer process in membrane distillation using a dense membrane will be similar to pervaporation, where the separation process is based on solubility and diffusivity. PEO-PBT polymer material (polyethylene oxide, poly (butyl terephthalate)) has a higher water vapor permeability coefficient compared to Cellulose Acetate (CA) and Polysulfone (PSf) in the use of asymmetric dense membranes. Nanocomposite membranes, inorganic materials, Janus membranes, and omniphobic membranes can also be considered to support the development of dense membranes in membrane distillation. .